Trace Determination of Rhodium in Coating Wastewater by Vortex Assisted Magnetic Nanoparticle Based Solid Phase Microextraction (MNP-SPME) Combined with Slotted Quartz Tube-Flame Atomic Absorption Spectrometry (SQT-FAAS) with Matrix Matching Calibration - Serbest, Hakan; Bakirdere, Sezgin; Keyf, Seyfullah (TAYLOR & FRANCIS INC, 2022)
A magnetic nanoparticle based solid phase microextraction method (MNP-SPME) was developed for the extraction/preconcentration of rhodium prior to determination by slotted quartz tube flame atomic absorption spectrometry (SQT-FAAS). The extraction efficiency was enhanced by the binary MNPs (uncoated MNPs and amidosulfonic acid coated MNPs). The parameters affecting rhodium extraction such as the pH and volume of buffer solution, mixing type/period after the addition MNPs and sample volume were optimized by univariate optimization. Box-Behnken design with five center points was also used as a multivariate approach for the determination of the optimum values of the MNP mass and percentages and eluent volume. Under the optimum conditions, the limits of detection and quantitation were 0.3 and 1.1 mu g L-1. In order to characterize the applicability/accuracy of the method, spiking experiments were performed in metal coating wastewater. Recoveries were between 95.5% and 102.9% using matrix matching calibration. The developed method achieved a 129.1-fold enhancement in detection power compared to FAAS. The recovery results demonstrated the accuracy of the developed strategy for the determination of rhodium in complex matrices.
Keywords: Amidosulfonic acid-coated magnetic nanoparticles; flame atomic absorption spectrometry; rhodium; slotted quartz tube; solid phase microextraction; LIQUID-LIQUID MICROEXTRACTION; ORIGINS UNTIL TODAY; ROAD DUST SAMPLES; ENVIRONMENTAL-SAMPLES; PLATINUM; PALLADIUM; PRECONCENTRATION; EXTRACTION; ION; CATALYSTS; Chemistry